Proposal for a structured computed tomography report in the evaluation of pancreatic neoplasms based on expert opinions - Lopes,Paulo Gustavo Maciel (2018)
Abstract Objective: To create a structured computed tomography (CT) report for the systematic evaluation of pancreatic ductal adenocarcinoma (PDAC), based on the opinions of clinicians and surgeons. Materials and Methods: This was a prospective study in which we applied a 21-item questionnaire to experts in pancreatic diseases in order to create a model of a structured abdominal CT report. The questionnaire addressed the location and size of PDACs, as well as their effects on adjacent structures and on the vasculature, together with metastases. We used a Likert scale to determine which of those parameters should be included in the model. Results: A total of 18 experts (12 surgeons and 6 clinicians) from 9 institutions completed the questionnaire. All of the experts agreed that the following (if present) should be described in the CT report on a PDAC: the degree of enhancement; the diameter and location of the lesion; pancreatic duct obstruction; biliary dilatation; pancreatic atrophy; liver metastases; peritoneal nodules; ascites; lymph node enlargement; and invasion of adjacent structures. More than 80% of the experts agreed that the report should also describe the relationship between the PDAC and the surrounding vasculature. Conclusion: We have developed a template for a CT report on patients with PDAC, based on the opinions of experts involved in the treatment of such patients.